Chloroplast phylogenomics of Calocedrus (Cupressaceae) - Xiao-Jian Qu (Mitochondrial DNA. Part B. Resources, 2019)
Calocedrus is a genus of the family Cupressaceae. Among this genus, C. decurrens is the only species native to western North America. In this study, the complete chloroplast genome (plastome) of C. decurrens was determined using Illumina sequencing platform. The plastome lacking one copy of inverted repeat (IR) was 127,112 bp in length. The plastome contained 118 unique genes, including 83 protein-coding genes (PCGs), 31 transfer RNA genes (tRNAs), and 4 ribosomal RNA genes (rRNAs). Nine PCGs and six tRNAs contained one intron each, two PCGs contained two introns each. The overall GC content of the plastome was 34.8%. Phylogenomic analysis of 24 representative plastome within the Cupressaceae family revealed that C. decurrens was sister to the remaining Calocedrus species, and C. rupestris was sister to the clade comprising of C. macrolepis and C. formosana.